Hubungan Penggunaan Tiktok Yang Berlebihan Terhadap Kesehatan Mental Pada Mahasiswa - Isak Iskandar; musfiroh, musfiroh (Jurnal Intelek Insan Cendikia, 2025)
This study examines how excessive TikTok usage correlates with the mental health status of college students. Using a quantitative correlational design, data collection involved online questionnaires that assessed how often and how long students used TikTok, alongside mental health assessments utilizing the DASS-21 instrument. The findings indicate that many students tend to open TikTok automatically, feel anxious when they are not engaged with the platform, and experience sleep disruptions because of extended use. The data suggests a moderate to high engagement level, which can potentially lead to psychological problems such as stress, anxiety, and depression. The research highlights the necessity of enhancing digital literacy, managing screen time effectively, and encouraging healthier digital habits to reduce adverse effects. Recommendations include awareness campaigns, educational programs, and support systems aimed at helping students control their media activity and sustain their mental well-being.